2010
DOI: 10.1017/s0008423910000065
|View full text |Cite
|
Sign up to set email alerts
|

Does Diversity Damage Social Capital? A Comparative Study of Neighbourhood Diversity and Social Capital in the US and Britain

Abstract: Abstract. A number of scholars have noted a negative relationship between ethnic diversity and social capital or social trust, especially in the US. Evidence from other countries has been more mixed and sometimes contradictory. In this paper we provide the first Anglo-American comparative analysis of the relationship between neighbourhood diversity and social capital, and show how this relationship varies across ethnic categories. We apply multilevel structural equation models to individual level data from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(104 citation statements)
references
References 42 publications
5
94
4
1
Order By: Relevance
“…Both strategies have been used in those, relatively few, studies that do not disregard members of minority groups altogether. Some of these studies report a weaker (Putnam, 2007;Stolle et al, 2008; similarly an earlier analysis of the data used in this paper, see Koopmans and Schaeffer, 2016), others no significant relation between diversity and social cohesion measures among minority members (Bakker & Dekker, 2012;Fieldhouse & Cutts, 2010). But while such analyses acknowledge the possibility of effect heterogeneity between majority and minority respondents, they still disregard another ambiguity of diversity indices.…”
Section: In-group Share and Relational Out-group Entropy Or Why Intesupporting
confidence: 49%
“…Both strategies have been used in those, relatively few, studies that do not disregard members of minority groups altogether. Some of these studies report a weaker (Putnam, 2007;Stolle et al, 2008; similarly an earlier analysis of the data used in this paper, see Koopmans and Schaeffer, 2016), others no significant relation between diversity and social cohesion measures among minority members (Bakker & Dekker, 2012;Fieldhouse & Cutts, 2010). But while such analyses acknowledge the possibility of effect heterogeneity between majority and minority respondents, they still disregard another ambiguity of diversity indices.…”
Section: In-group Share and Relational Out-group Entropy Or Why Intesupporting
confidence: 49%
“…This is particularly the case in the UK. Whilst many British studies stress the relatively weaker effects of community diversity on social capital compared to levels of deprivation, each still observe that, on the whole, living in more diverse communities has a significant negative relationship with attitudes towards one's neighbours, especially trust in neighbours (Bécares et al, 2011;Fieldhouse & Cutts, 2010;Laurence, 2011;Letki, 2008;Sturgis et al, 2011;Twigg et al, 2010). Based on the similarity of these findings to Putnam's (2007) neighbourhood trust finding we might conclude that in Great Britain higher ethnic diversity undermines social capital.…”
Section: Theoretical Framework: Issues With the Current Literaturementioning
confidence: 89%
“…And one must concede that this is a reasonable summary, insofar as it relates to studies that have examined the association between ethnic heterogeneity at some level of geographical aggregation and the expressed attitudes and behaviours of individual residents. For, while some scholars have found positive (Marschall and Stolle 2004;Mata 2012) or non-significant (Aizlewood andPendakur 2005;Leigh 2006;Soroka, Johnston, and Banting 2007;) effects of diversity on generalized trust, the large majority of studies have found significant negative associations between diversity and measures of prosocial attitudes (Knack and Keefer 1997;Pennant 2005;Putnam 2007;Letki 2008;Fieldhouse and Cutts 2010;Becares et al Ethnic andRacial Studies 1289 2011). And, although the magnitude of the relationship appears to vary across ethnic groups, the basic pattern of negative association between diversity and social capital is broadly consistent across North America and the European contexts in which it has been examined (Fieldhouse and Cutts 2010;Lancee and Dronkers 2011).…”
Section: Ethnic Diversity and Social Cohesion: Existing Evidencementioning
confidence: 99%